SOME NON CHEMICAL METHODS TO CONTROL BLACK SCURF DISEASE OF POTATO CAUSED BY Rhizoctonia solani - Oadi N. Matny (Mesopotamia Journal of Agriculture)
This study was carried out in the fields of Plant Protection Department-College of Agriculture/University of Baghdad, during spring season 2010-2011, to test the efficiency of some biological factors and fermented neem extract to control black scurf disease caused by Rhizoctonia solani in Burien potato cultivar.The study showed the superiority of biological agent Biocont (Trichoderma harzianum) and the yeasts S.cerevisia and Rhodotorula sp and the fermented neem extract and bacteria P.fluorescens in reducing the percent infection of tubers, as amounting to 5, 5, 5, 60 and 100% respectively, rate of the canker symptoms in the main stem of plants, it was 5, 5, 5, 20 and 60% respectively, and disease severity on tubers at 10, 12, 9, 30, 5 and 75%, respectively. All tested agents showed significant increase in the rate of yield/plant, which was recoreded at 590, 395, 450, 495, 530 and 214 g each to the treatments Biocont and yeasts S.cerevisia, Rhodotorula sp and the bacteria P.fluorescens and fermented neem extract and the pathogen (R.solani only), respectively.